2021
DOI: 10.1021/acs.jced.1c00050
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Behavior and Synergistic Solvation Effects of N-Benzylglycine in Eleven Neat and One Binary Solvent Systems from 283.15 to 323.15 K

Abstract: The equilibrium solubility of N-benzylglycine in 11 pure solvents (methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, acetone, acetonitrile, dichloromethane, ethyl acetate, 1,4-dioxane, and water) and one binary water + ethanol solvent mixture was measured by a static gravimetric method covering the temperature range of (283.15−323.15) K. The polymorphism of N-benzylglycine was characterized via the powder X-ray diffraction test and the results indicate that no crystal form transition occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…For alcohols, it can be seen that the mole fraction solubility of Glu-Me in these solvents, from high to low, was in the order: methanol > ethanol > 2-propanol > 1-propanol at the lower temperature from 283.15 to 308.15 K, but when T > 308.15 K, this order becomes methanol > ethanol > 1-propanol > 2-propanol. The polarity is entirely consistent with the solubility order of Glu-Me in these alcohol solvents at high temperatures ( T > 308.15 K), following the principle of “similar compatibility”. , Moreover, it has been reported that the larger alkyl groups increased the hydrophobic effect, resulting in a decrease in solubility . Due to the presence of the ethyl group in the molecular structure of 1-propanol, this may result in a lower solubility value than that of 2-propanol at low temperatures ( T < 308.15).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…For alcohols, it can be seen that the mole fraction solubility of Glu-Me in these solvents, from high to low, was in the order: methanol > ethanol > 2-propanol > 1-propanol at the lower temperature from 283.15 to 308.15 K, but when T > 308.15 K, this order becomes methanol > ethanol > 1-propanol > 2-propanol. The polarity is entirely consistent with the solubility order of Glu-Me in these alcohol solvents at high temperatures ( T > 308.15 K), following the principle of “similar compatibility”. , Moreover, it has been reported that the larger alkyl groups increased the hydrophobic effect, resulting in a decrease in solubility . Due to the presence of the ethyl group in the molecular structure of 1-propanol, this may result in a lower solubility value than that of 2-propanol at low temperatures ( T < 308.15).…”
Section: Resultssupporting
confidence: 75%
“…The polarity is entirely consistent with the solubility order of Glu-Me in these alcohol solvents at high temperatures (T > 308.15 K), following the principle of "similar compatibility". 27,51 Moreover, it has been reported that the larger alkyl groups increased the hydrophobic effect, resulting in a decrease in solubility. 52 Due to the presence of the ethyl group in the molecular structure of 1-propanol, this may result in a lower solubility value than that of 2-propanol at low temperatures (T < 308.15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the raw materials used for measuring the Boc- l -glutamine solubility are given in Table , and none of the chemicals have been further purified. The mole fraction solubility of Boc- l -glutamine in pure solvents was measured by the static gravimetric method, which has been described , and validated in previous works. In addition, the experimental equipment and detailed procedures for solubility measurement are presented in the Supporting Information.…”
Section: Methodsmentioning
confidence: 96%
“…In order to determine whether the equilibrium state of solid N α -carbobenzyloxy- l -arginine changes in different solvent systems, powder X-ray diffraction (PXRD) was used to analyze the raw material and the equilibrium solid samples. The preparation method of the sample has been described in the Supporting Information and our previous work . PXRD (PANalytical B.V. X’Pert PRO MPD, Netherlands) uses an X-ray generator with Cu Ka radiation (1.5406 Å) at a scanning rate of 10° per minute, and the data were collected from 5 to 60° at 2θ degree.…”
Section: Methodsmentioning
confidence: 99%